Preliminary report on use of depot formulation of LHRH analogue ICI 118630 (Zoladex) in patients with prostatic cancer. Issue 6463 (19th January 1985) - Ahmed, S R; Grant, J; Shalet, S M; Howell, A; Chowdhury, S D; Weatherson, T; Blacklock, N J
Abstract : A study was conducted of the response of the pituitary-testicular axis to two different methods of administration of the luteinising hormone releasing hormone (LHRH) analogue ICI 118630 (Zoladex) in patients with prostatic cancer. The analogue was given by continuous infusion to four previously untreated patients with prostatic cancer for 60 days (group 1). Subsequently a further four patients were given a depot formulation of the same analogue by subcutaneous injection once every 28 days (group 2). Both methods of administration produced similar, successful suppression of luteinising hormone (LH) associated with a reduction of testosterone to castrate concentrations. The median basal testosterone concentrations before treatment in groups 1 and 2 were 20.6 and 14.1 nmol/l (5.94 and 4.07 ng/ml) respectively; these were reduced to 1.4 and 1.1 nmol/l (0.40 and 0.32 ng/ml) within four weeks of the start of treatment. The median basal LH concentration in groups 1 and 2 were 7.9 and 16.6 IU/1 respectively, which were suppressed to 2.6 and 2.4 IU/1 by four weeks. The suppression of LH and testosterone was maintained with continuous subcutaneous infusion for up to 60 days in group 1, and by subsequent injections of the depot every 28 days in group 2. The use of depot preparation of an LHRH analogue to suppress gonadotrophin and sex hormone secretion offers the convenience of once monthly injections when LHRH analogues are required for the long term treatment of elderly patients with prostatic cancer and children with precocious puberty.